BS EN IEC 61557-10 . Electrical safety in low voltage distribution systems up to 1 000 V AC and 1 500 V DC. Equipment for testing, measuring or monitoring of protective measures. Part 10. Combined measuring equipment (1st September 2023) - British Standards Institution
No abstract available